The Use of Principal Components Analysis in the Formation of a Sustainable Human Development Index for Arab Countries - الشيخ, ساوس; الهاشمي, ربيعي (Journal of Economics and Administrative Sciences, 2025)
This study aims to derive a sustainable human development index for the Arab countries by using the principal components analysis, which can help in reducing the number of data in the case of multiple variables.  This can be relied upon in the interpretation and tracking sustainable human development in the Arab countries in the view of the multiplicity of sustainable human development indicators and its huge data, beside the heterogeneity of countries in a range of characteristics associated with indicators of sustainable human development such as area, population, and economic activity. The study attempted to use the available data to the selected Arab countries for the recent years. This study concluded that a single index or a set of sustainable human development indices can be derived for interpretation is better than dealing with different sustainable human development indices individually and independently.